Audit timeliness and market capitalization: Evidence from an emerging market - Mizdraković, Vule M; Gligorić, Maja; Mitrašinović, Ivana; Bošković Marković, Valentina (Industrija, 2019)
This paper analyses the lag of audit reports for companies included on Belgrade Stock Exchange (BELEX). Its purpose is to define which of listed variables have an influence on the length of time between the end of the financial reporting period and the date the audit report is made public. The research sample includes 400 firm year observations for 2017, representing approximately 70% of the total number of public companies on the BELEX. The results are interpreted through descriptive analysis, correlation analysis between the given variables, and linear regression. Based on these results, the authors created a model which highlights critical factors in estimating Audit Report Lag (ARL). Research results have shown that the level of market capitalization represents a statistically significant variable for predicting ARL. Companies with higher market capitalization can expect reports more quickly than other companies. Research results may assist prospective and existing investors when analysing investment risks related to the accuracy and reliability of information presented in financial statements. Regarding its contribution, this paper is considered original as it is the first paper that analyses the factors affecting ARL in the Republic of Serbia.